Hot melt granulation method for the preparation of floating matrix tablets of Tolperison Hydrochloride - Ankita U. Patel; Dipti V. Caudhari; Pranav J. Shah; Shailesh A. Shah (SpringerOpen, 2018)
Tolperisone HCl is a centrally muscles relaxant drug. It is a highly water-soluble drug. It has a biological half-life of 1.5-2.5 h. It has absorption window in the small intestine and unstable in intestinal pH 4 to 7. Gastroretentive drug delivery systems have shown to be of better significance in controlling release rate for drug having site specific absorption. The aim of the present investigation was to develop effervescent floating matrix tablets of Tolperisone Hydrochloride. Cetyl alcohol was selected to prepare hot melt granules (HMG) of Tolperisone HCl. Effervescent floating matrix tablet was prepared using cetyl alcohol as lipophilic surfactant and HPMC K100M as hydrophilic polymers. The HMG based floating matrix tablets were optimized by 32 full factorial design to study the effect of independent variables, i.e. amount of cetyl alcohol (X1) and amount of HPMC K100M (X2) on dependent variables like % swelling index (Y1), time required to 50% drug released(t50)(Y2) and time required for 90% drug release (t90)(Y3). From the regression analysis, it was observed that selected two independent variables show significant effect on response variables. From the results obtained, F10 formulation (58.10 mg of cetyl alcohol, 147.18 mg of HPMC K100M) was selected as optimized batch which showed optimum floating lag time (14 s), drug content (102.78 ± 2.15%), %swelling index (182.63 ± 2.15 at 12 h), t50 (310.2 min) and t90(649.8 min). Thus, the effervescent floating matrix tablets based on HMG is suitable to get site specific delivery and controlled release of Tolperisone HCl. Keywords: Cetyl alcohol, Effervescent floating tablets, Hot melt granulation, HPMC K100M, Tolperisone HCl